The Influence of Risk and The Crowdfunding Ecosystem on Investment Decision Behavior: The Role of Financial Literacy - Yuliana Jasuni, Ana; Ramadhan, Reka (The Eastasouth Management and Business, 2024)
One way to support the government's smooth running of inclusive economic development is to help MSMEs (Micro, Small, and Medium Enterprises) gain access to funding. Along with technological developments, there is a new way for people to obtain external funding, namely through Crowdfunding Services. Crowdfunding has enormous potential in terms of helping people (especially MSMEs) to get external funds to develop their businesses. This research aims to analyze the influence of risk and the crowdfunding ecosystem on investment decision behavior in several crowdfunding companies in Indonesia with financial literacy as a moderating variable. The objectives of the research will be achieved using a problem-solving approach empirical and quantitative analysis. The research results show that risk and the crowdfunding ecosystem have a significant influence on investment decision behavior. The results of this research will be distributed to member companies of the Indonesian Sharia Fintech Association (AFSI) and it is hoped that it will provide information that helps them make decisions.